Legal Harmonisation in BRICS: Analysing Cross-Border Trade Rules and Dispute Settlement Mechanisms - Haryono Haryono; Woro Utari; Diah Ayu Rahmawati; Budi Endarto; Joice Soraya (West Science Social and Humanities Studies, 2024)
This study explores the legal harmonization of cross-border trade regulations and dispute settlement mechanisms within the BRICS bloc, comprising Brazil, Russia, India, China, and South Africa. With diverse legal traditions and economic priorities, BRICS nations face significant challenges in aligning their legal frameworks to foster seamless trade and effective dispute resolution. Using a normative juridical approach, this research examines regulatory disparities, existing dispute resolution mechanisms, and the potential for harmonization. The findings highlight key barriers, such as fragmented legal systems, inconsistent enforcement, and limited institutional capacity, while proposing actionable strategies, including standardized tariff systems, mutual recognition agreements, and the establishment of a centralized arbitration body. By addressing these issues, the study underscores the importance of legal alignment for enhancing economic integration and strengthening BRICS' position in global trade.